Evaluation of various nephrometric scoring system for nephrolithiasis to predict stone free status after percutaneous nephrolithotomy: A comparative study. Issue 3 (August 2022) - Chatterjee, Souvik; Abhishek, Anand; Samanta, Kaniska; Ghosh, Anupama; Mandal, Soumendra Nath; Karmakar, Dilip
Background: The CROES Nephrolithometry nomogram, S.T.O.N.E. Nephrolithometry Score and Guy's stone score were introduced for stratification of kidney stones disease on the basis of quantitative stone burden and its distribution. Till date there has been very limited data on head to head comparison of the existing scoring systems. Comparison and analyses among the scoring system helps in further refinement of these systems along with development of new more effective and broadly acceptable nomogram. Objective: Predictability of the stone-free status (SFS) and post-operative complication after PCNL by various scoring systems (The CROES nomogram, S.T.O.N.E. nephrolithometry score and Guy's stone score). Materials and Methods: Total 100 adult patients underwent PCNL after considering inclusion and exclusion criteria. All patients underwent Preoperative NCCT scan, investigations of blood (Hb%, PCV, bleeding and coagulation profile, urea, and creatinine), and urine (RE/ME and C/S), Postoperative X ray KUB/NCCT. Results: ROC curves were developed for each scoring system to determine the accuracy to predict stone free status. We found CS had significantly higher AUC than other scoring systems [ p -value for CS vs GSS = 0.0091 & CS vs SS = 0.000]. So CS has higher accuracy to predict stone free status. None of the scoring system had shown significantly higher AUC than other scoring system in predicting complication. Conclusion: CROES Nephrolithometry nomogram is most accurate to predict preoperative stone-free rate. All scoring systems can equally predict perioperative complications and other variables.